Forms and Methods of Protecting the Social Rights of Military Personnel in Ukraine - Рекшинський Володимир Орестович (My University, 2024)
The dissertation work is a scientific study that conducts a comprehensive analysis of the content, forms, and methods of protecting the social rights of military personnel. It also identifies the problems associated with these rights and formulates effective, comprehensive solutions. The work has enhanced both the theoretical and practical understanding of the social rights of military personnel in Ukraine. It frames these rights as a socially and morally justified compilation of universal human and social demands pertinent to the social and legal status of military personnel, as defined by legislation. These rights are deemed essential for a full human life. It is determined that the spectrum of social rights for military personnel includes special social rights specific to military service, alongside fundamental social human rights and basic social rights of military personnel (as employees). These rights are encompassed within the broader social and legal status of military personnel. The dissertation characterizes the conceptual content and social and legal significance of protecting the social rights of military personnel as a purposeful activity of entities, objectified in legally defined forms and employing legal methods to stop violations of social rights, confirm, or restore a contested or violated subjective right of a serviceman. This jurisdictional (and non-jurisdictional) activity is marked by its social and legal importance for several reasons. First, it is a legally significant act that restores law and order and social justice, which also results in affirming the social security of both the military personnel and the state (society). Second, it is a civilizationally balanced, socially fair, and socially responsible act that recognizes and upholds the human dignity of military personnel. Third, it serves as a means (instrument) that not only facilitates access to benefits restricted by the violation of subjective social law but also ensures the holistic existence of the military person as an individual, citizen, and worker (employee), maintaining a balance between social rights and other human rights. Fourth, it provides a platform where the negative effects on the state’s defense capability, resulting from inadequate fulfillment of the state’s social function towards military personnel, are minimized and eliminated. The scientific discourse regarding the essential content of the forms and methods used to protect the social rights of military personnel in Ukraine has been further developed. The appropriate forms are viewed as external expressions of the activities of an authorized entity, aligning with legal principles and regulated by existing legislation. The author discusses activities aimed at restoring, establishing, and recognizing the subjective social rights of military personnel within the bounds of the applicable procedural framework. These activities also encompass material, moral, or organizational and legal compensation for the violated rights and efforts to prevent further violations of military personnel’s rights. The means (methods) of protecting the social rights of military personnel comprise a set of techniques and procedures stipulated by law and executed by an authorized entity within a specified form of social rights protection. The dissertation provides detailed analysis of the features of the modern theoretical and legal understanding of the content and issues of jurisdictional forms of protecting the rights of military personnel in Ukraine. It identifies that the judicial form of protection of social rights for military personnel is considered the most effective. However, its effectiveness in ensuring human rights is diminished by factors such as complicated access to justice for military personnel located in combat zones and the non-execution or untimely execution of court decisions relating to violated social rights of military personnel. Additionally, the parliamentary form of protection of the social rights of military personnel holds significant human rights potential. Yet, this potential is undermined by the absence of adequate guarantees for fulfilling the legal requirements set by the Commissioner of the Verkhovna Rada of Ukraine for Human Rights. Therefore, the recommendation is that the creation of the position of Commissioner for the Rights of Military Personnel should be accompanied by a parallel strengthening of guarantees for the control activities of the Ombudsman. The administrative form of protection of social rights also requires formalization to meet the requirements of the principle of legal certainty and to clearly specify methods for protecting the social rights of military personnel within this jurisdictional framework. Non-jurisdictional forms of protecting the social rights of military personnel hold a unique socio-legal significance, playing a critical role in ensuring their social security due to their protective potential. However, unlike other workers, these employees face significant limitations in their ability to self-defend their social rights – except in cases of refusing to execute an illegal order – as such; actions may negatively affect the state’s defense capabilities. This restriction on the choice of non-jurisdictional protection methods can be compensated for by adopting a legislative act on mediation in the field of ensuring social and related rights of military personnel and creating institutional conditions for the activities of mediators who specialize in protecting the social (also labor) rights of military personnel. To enhance the effectiveness of extra-jurisdictional forms of protecting the social rights of military personnel, it is also essential to strengthen guarantees for the activities of civil society actors, primarily trade unions and military associations, to protect these rights. These measures would help address the gaps in protection and ensure a more robust framework for the safeguarding of military personnel’s rights. The approach to defining the actual characteristics of the structure of modern methods for protecting the social rights of military personnel in Ukraine has been refined. This approach primarily includes the following elements: recognition of social law and its scope, as well as documentation of the temporal circumstances of the emergence of this subjective right and the instances of its violation; cessation of actions that infringe upon the social rights of military personnel and prevention of their future recurrence; restoration of conditions that allow military personnel to reclaim and subsequently exercise their rights following violations; acknowledgment of the illegality of actions and decisions (including agreements) that constitute the factual basis for the violation of social rights of military personnel. This also entails the annulment of the relevant decisions and agreements in whole or in part; termination or modification of legal relations that have led to the infringement of the social rights of military personnel; and compensation for damages and restitution for harm caused by the violation of social rights. To effectively protect the social rights of military personnel, these methods need to be comprehensively regulated within a special legislative act dedicated to ensuring the social security of military personnel. This act should detail the procedures and mechanisms for the recognition, protection, and restoration of these rights, ensuring that military personnel are adequately safeguarded within the legal framework. The analysis of the legal regulation concerning the protection of the rights of military personnel in the United States has been conducted. In the U.S., the protection of the social rights of military personnel is ensured both judicially and non-judicially (formerly administratively) based on the provisions of the U.S. Constitution (specifically the Fifth and Fourteenth Amendments), as well as Chapter 47, Section 10, Section 28, Part III of Title 38 of the U.S. Code, and special legislative acts related to social security. Case law, including significant Supreme Court decisions such as Orloff v. Willoughby and Levin v. United States, also plays a crucial role in shaping these protections. Although the Uniform Code of Military Justice imposes limitations on the trade union rights of military personnel, this restriction is offset by the servicemen’s right to seek the protection of their social rights through associations of military personnel. These associations are actively involved in human rights advocacy and lobbying activities in the U.S., particularly focusing on social issues, thus providing an effective mechanism for addressing and safeguarding the rights of military personnel. The current state of legal regulation concerning the protection of the social rights of military personnel within individual member states of the European Union has been distinctly identified. It is noted that in France, both typical jurisdictional and non-jurisdictional forms of protecting the social rights of military personnel are prevalent. Additionally, the option of mediation is available, wherein a military mediator can become involved in the process of protecting a serviceman’s social rights. However, French law restricts the right of military personnel to defend their social rights through trade union protection, a concern that has repeatedly been brought to the attention of the European Court of Human Rights. In several European countries, the trade union form of protection for social rights is prevalent, and in the absence of such unions, protection is provided by military associations. Specifically, in Hungary, where trade union protection for the social rights of military personnel was anticipated, legislative changes scheduled for 2023 aim at dismantling trade unions, thus eliminating this form of protection. This shift represents a significant change in the legal framework governing the protection of military personnel’s rights within the country. It is advisable to improve the legal regulation of forms and methods for protecting the social rights of military personnel in Ukraine through three strategic directions. The first direction is conceptual and strategic, involving the creation of a comprehensive concept and strategy to ensure the social security of military personnel, along with a specific strategy to foster gender equality within the security and defense sector. The second direction focuses on law-making, which encompasses several legislative initiatives. These include the creation and adoption of a specialized legislative act dedicated to the social security of military personnel, which will feature a detailed section on the protection of their social rights, covering principles, forms, methods, means, grounds, conditions, and guarantees. Another legislative measure to be introduced is an act concerning civil society, which will define the human rights activities of civil society actors. Amendments to the existing legislation on the Ombudsman will also be introduced to strengthen the legal guarantees for his human rights activities. Additionally, a formal procedure will be established for military personnel to challenge actions (or inactions) and decisions made by leaders in the security and defense sector. The third direction involves the legal and regulatory support for expanding the institutional framework to protect the social rights of military personnel. This expansion includes the creation and adoption of legislative acts that establish the legal status and procedural guidelines for roles such as a mediator in the military and defense sector and a Commissioner of the Verkhovna Rada of Ukraine for the rights of military personnel, complementing the effectiveness of the Ombudsman’s office.

Дисертаційна робота є науковим дослідженням, що присвячено цілісному аналізу змісту та особливостей форм і способів захисту соціальних прав військовослужбовців, а також визначенню їх проблем і формулюванню ефективних шляхів їх комплексного вирішення. У роботі вдосконалено теоретично-практичне осмислення змісту соціальних прав військовослужбовців в Україні, як соціально та морально обґрунтованого, визначеного на законодавчому рівні переліку об’єктивно необхідних для повноцінного життя людини загальнолюдських і загальносоціальних вимог до соціально-правового стану кожного військовослужбовця. Встановлюється, що перелік соціальних прав військовослужбовців складають спеціальні соціальні права військовослужбовця, а також базові соціальні права людини і основні соціальні права військовослужбовця (як працівника), що можуть бути охоплені соціально-правовим статусом військовослужбовця. Окремо дана характеристика концептуальному змісту та соціально-правовому значенню захисту соціальних прав військовослужбовців, як цілеспрямованої діяльності правозастосовних суб’єктів, що об’єктивується у формах, визначених законодавством, а також із використанням законних способів захисту прав у соціальній сфері з метою припинення порушення соціальних прав, підтвердження або відновлення порушеного (оспорюваного) суб’єктивного права військовослужбовця. Ця юрисдикційна (також неюрисдикційна) діяльність характеризується соціально-правовим значенням адже є: юридично значимим актом відновлення правопорядку та соціальної справедливості, наслідком чого також є утвердження соціальної безпеки військовослужбовця та держави (суспільства); цивілізаційно зваженим, соціально справедливим та соціально відповідальним актом визнання за військовослужбовцем людської гідності; засобом (інструментом), що не лише дозволяє задовольнити блага, доступ до яких був обмежений порушенням суб’єктивного соціального права, але й забезпечує повноцінне буття військовослужбовця як людини, громадянина та працівника (службовця), враховуючи при цьому кореляційний зв’язок соціальних прав з ін. правами людини; площиною, на якій мінімізується та усувається негативний вплив на обороноздатність держави через недостатню реалізацію соціальної функції держави щодо військовослужбовців. Дістала подальшого розвитку наукова думка щодо сутнісного змісту форм і способів захисту соціальних прав військовослужбовців в Україні. Відповідними формами є узгоджені із принципами права та регламентовані чинним законодавством зовнішні вирази діяльності повноваженого суб’єкта, спрямованої на поновлення, встановлення та визнання суб’єктивних соціальних прав військовослужбовців у межах відповідної процедури (процесу), а також на подальшу матеріальну, моральну чи організаційно-правову компенсацію порушеного права та запобігання подальшого порушення прав військовослужбовця. Способами захисту соціальних прав військовослужбовців постає сукупність прийомів і процедур, що передбачені законодавством і здійснюються повноважним суб’єктом у межах певної форми захисту соціальних прав. Детальна увага в дисертації звертається на особливості сучасного теоретико-правового розуміння змісту та проблематики юрисдикційних форм захисту соціальних прав військовослужбовців в Україні. Встановлюється, що судова форма захисту соціальних прав військовослужбовців вважається найбільш ефективною, проте, її правозахисний ефект послаблюється: ускладненим доступом до правосуддя військовослужбовців, які перебувають в зоні бойових дій; невиконанням (невчасним виконанням) державою ряду судових рішень, які стосуються порушених соціальних прав військовослужбовців та ін. Парламентська форма захисту соціальних прав військовослужбовців має значний правозахисний потенціал, проте, він нівелюється відсутністю належних гарантій виконання законних вимог Уповноваженого Верховної Ради України з прав людини, а тому, подальше створення посади Уповноваженого з прав військовослужбовців повинно відбуватись з паралельним посиленням гарантій контрольної діяльності Омбудсмана. Адміністративна форма захисту соціальних прав наразі потребує формалізації у контексті забезпечення вимог принципу юридичної визначеності, а також конкретизації способів захисту соціальних прав військовослужбовців у межах цієї форми захисту. Позаюрисдикційні форми захисту соціальних прав військовослужбовців мають унікальне соціально-правове значення, надаючи значний вплив на забезпечення їх соціальної безпеки завдяки своєму захисному потенціалу. Утім, на відміну від інших працівників, ці службовці фактично обмежені в можливості самозахисту своїх соціальних прав (за винятком випадків відмови від виконання незаконного наказу), оскільки це може негативно позначитися на обороноздатності держави. Таке обмеження широти вибору форм неюрисдикційного захисту соціальних прав може бути компенсованим шляхом: прийняття законодавчого акту про медіацію у сфері забезпечення соціальних та суміжних прав військовослужбовців; створення інституційних умов для діяльності медіаторів, які спеціалізуватимуться на захисті соціальних (також трудових) прав військовослужбовців. Для посилення ефективності позаюрисдикційних форм захисту соціальних прав військовослужбовців необхідним також є посилення гарантій діяльності із захисту соціальних прав суб’єктами громадянського суспільства (насамперед профспілками та асоціаціями військовослужбовців). Уточняється підхід до окреслення актуальної характеристики структури сучасних способів захисту соціальних прав військовослужбовців в Україні, якою охоплюється насамперед: визнання соціального права та його обсягу, а також констатація темпоральних обставин виникнення цього суб’єктивного права та обставин його порушення; припинення дій, якими вчиняється порушення соціальних прав військовослужбовців, а також попередження їх подальшого повторення щодо військовослужбовця; відновлення умов набуття та подальшої реалізації військовослужбовцем його соціальних прав, що були порушені; визнання протиправності дій та рішень (договорів), які є фактичною підставою порушення соціальних прав військовослужбовців (у результаті цього також: скасування відповідних рішень, договорів у цілому чи у певній частині; припинення чи зміна правовідносин, які стали правовою основою порушення соціальних прав військовослужбовця); відшкодування збитків і компенсація шкоди, які обумовлені порушенням соціальних прав. Способи захисту соціальних прав військовослужбовців потребують детальної регламентації у спеціальному законодавчому акті про забезпечення соціальної безпеки військовослужбовців. Здійснюється аналіз правового регулювання захисту соціальних прав військовослужбовців у Сполучених Штатах Америки. У США захист соціальних прав військовослужбовців здійснюється в судовому та позасудовому (насамперед адміністративному) порядку на підставі Конституції США (на основі П’ятої та Чотирнадцятої поправки), Глави 47 Розділу 10, Розділу 28, Частини ІІІ Розділу 38 Кодексу США, спеціальних законодавчих актів у сфері соціальної безпеки, прецедентної практики (зокрема, рішення ВС у справах, Орлов проти Віллоубі, Левін проти США). У Єдиному кодексі військової юстиції прямо обмежуються профспілкові права військовослужбовців, однак це обмеження компенсується правом на звернення військовослужбовця за захистом його соціальних прав до асоціацій військовослужбовців, які ефективно провадять у США правозахисну та лобістську діяльність (щонайперше у соціальній сфері). Окремо з’ясовано поточний стан правового регулювання захисту соціальних прав військовослужбовців в окремих державах державах-членах Європейського Союзу. Встановлюється, що зокрема у Франції існують типові юрисдикційні та позаюрисдикційні форми захисту соціальних прав військовослужбовців, однак: також передбачена можливість медіації, в рамках якої у процес захисту соціальних прав військовослужбовця може долучитись військовий посередник; законодавчо визначено обмеження військовослужбовців у праві захищати соціальні права в рамках профспілкового захисту, що є проблемою, на яку неодноразово звертав увагу ЄСПЛ. У ряді європейських країн існує профспілкова форма захисту соціальних прав, а в разі її відсутності, вона замінюється захистом з боку асоціацій військовослужбовців. В окремих державах, зокрема в Угорщині, де передбачався профспілковий захист соціальних прав військовослужбовців, з 2023 року вносяться зміни до законодавства, спрямованих на ліквідацію профспілок, що тягне за собою й ліквідацію цієї форми захисту. Удосконалення правового регулювання форм та способів захисту соціальних прав військовослужбовців в Україні доцільно здійснювати у трьох напрямах. Перший – концептуально-стратегічний (створення концепції та стратегії забезпечення соціальної безпеки військовослужбовців; створення Стратегії забезпечення гендерної рівності в секторі безпеки і оборони). Другий – правотворчий, яким охоплено, зокрема: створення та прийняття спеціального законодавчого акту про забезпечення соціальної безпеки військовослужбовців, окремий розділ якого буде присвячений захисту соціальних прав, а саме принципам, формам, способам, засобам, підставам, умовам та ін. гарантіям захисту соціальних прав; створення та прийняття законодавчого акту про громадянське суспільство, в якому буде визначена правозахисна діяльність суб’єктів громадянського суспільства; внесення змін до законодавства про Омбудсмана у частині посилення юридичних гарантій його правозахисної діяльності; створення порядку оскарження військовослужбовцем дій (бездіяльності) та рішень керівників у секторі безпеки і оборони. Третій – нормативно-правове забезпечення розширення інституційної основи захисту соціальних прав військовослужбовців, в рамках якого передбачено створення та прийняття законодавчих актів, що визначатимуть правовий статус і порядок діяльності: по-перше, медіатора у воєнному та оборонному секторі; по-друге, Уповноваженого Верховної Ради України з прав військовослужбовців, приймаючи до уваги переваги та недоліки забезпечення діяльності Омбудсмана.
Форми та способи захисту соціальних прав військовослужбовців в Україні
Keywords: військовослужбовці; Омбудсман; реформа законодавства; соціальна безпека; соціальна держава; соціальне право; соціальний захист; соціальні права; способи захисту; суб’єкти громадянського суспільства; суд; civil society actors; court; legislative reform; methods of protection; military personnel; Ombudsman; social law; social protection; social rights; social security; welfare state